Analyze The Effect of Service Quality, The Role of Social Media Technology, and Company Reputation On Increasing Power Sales - Reza Ardiansyah (Publikasi Indonesia, 2024)
The purpose of the research to identify effect of service quality, the role of social media technology, and company reputation on increasing power sales. This research is an explanatory research using hypothesis testing methods and quantitative approaches. The goal is to explain the causal relationship between one variable that affects another variable, namely independent variables in the form of service quality, the role of social media technology and company reputation on the dependent variable that is increased sales. Based on the discussion in the previous chapters and answering the problem formulation, research objectives and referring to the process and results of data analysis in this study, the following conclusions can be drawn: There is a positive and significant influence between service quality and increased electricity sales at PLN UP3 Ponorogo. There is a positive and significant influence between the role of social media technology and the increase in electricity sales at PLN UP3 Ponorogo. There is a positive and significant influence between the company's reputation and the increase in electricity sales at PLN UP3 Ponorogo